IMPLEMENTING DSS FOR SELECTING SUITABLE DELIVERY SERVICES TO SUPPORT SMART E-COMMERCE. - Bonang Waspadadi Ligar, Lintang Yuniar Banowosari (International Journal of Research Science and Management, 2018)
One of vital characteristics of smart e-commerce is the ability of providing real-time multicriteria decision making for the best possible delivery service. Success in the e-commerce sector is partly determined by delivery service qualities, including price, safety, speed, traceability and friendliness that contribute to the satisfaction of customers. This paper discusses the provision of a multicriteria decision making tool that enables customers to examine and choose, with certitude, the best possible delivery service. The proposed DSS is based on an AHP method comprising three structured muti-criteria and sub-criteria for selecting the best possible choice from a set of alternatives. The DSS has been tested for three famous providers of delivery services in Indonesia, including JNE, TIKI and Pos Indonesia.